PERCAKAPAN DARI RUANG TAMU: SEBUAH PENELUSURAN PUSTAKA ANTROPOLOGIS - Handoni, Hilman (Studi Budaya Nusantara, 2023)
This article traces anthropological studies related to living rooms starting from the classical period at the end of thenineteenth century to the contemporary period. Studies about the living room are usually overshadowed by the large frame of studies about the house or space in general. In classical anthropological studies, the house is usually discussed more from the aspect of its vernacular traditions including daily life, kinship patterns, symbolic structures, beliefs and ritual practices that occur and are centered in the house. The house, including the living room, is assumed to be the final form, complete with walls and partitions, which is ready to be analyzed. Meanwhile, in contemporary studies, space and home are considered inseparable from the global forces, competition for space, planning, politics and funding that shape them. (Guest) space is also a collection of human experiences that are formed from various relationships and are influenced by human and non-human actors. Space in the contemporary tradition is also considered as an experience involving the human body, which has emotions and affection, which isactively capable of transforming the meaning of a space. This investigation also found that there are still not many studies regarding space (guests) in dense urban-village areas characterized by conflict and struggle for space in anthropological studies. The richness of this perspective can be used as capital in reviewing the complexity of a cultural phenomenon called the living room.